2014
DOI: 10.1369/0022155414551367
|View full text |Cite
|
Sign up to set email alerts
|

The Adaptor Protein p62 Is Involved in RANKL-induced Autophagy and Osteoclastogenesis

Abstract: Previous studies have implicated autophagy in osteoclast differentiation. The aim of this study was to investigate the potential role of p62, a characterized adaptor protein for autophagy, in RANKL-induced osteoclastogenesis. Real-time quantitative PCR and western blot analyses were used to evaluate the expression levels of autophagy-related markers during RANKL-induced osteoclastogenesis in mouse macrophage-like RAW264.7 cells. Meanwhile, the potential relationship between p62/LC3 localization and F-actin rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 41 publications
3
51
0
Order By: Relevance
“…p62 is a multifunctional protein containing a number of protein‐protein interaction motifs that are involved in protein aggregation and degradation . It has been reported that autophagy dysfunction or defects will cause p62 upregulation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…p62 is a multifunctional protein containing a number of protein‐protein interaction motifs that are involved in protein aggregation and degradation . It has been reported that autophagy dysfunction or defects will cause p62 upregulation .…”
Section: Discussionmentioning
confidence: 99%
“…p62 is a multifunctional protein containing a number of protein-protein interaction motifs that are involved in protein aggregation and degradation. 24 It has been reported that autophagy dysfunction or defects will cause p62 upregulation. 25 Based on evidence of p62 partial restoration, recent research proved that chloroquine is an autophagy inhibitor and further increases LC3II/LC3I expression in rats.…”
Section: Discussionmentioning
confidence: 99%
“…[62][63][64] Studies indicate that autophagy also plays an important role in bone resorption by osteoclasts. 65 It has been reported that proteins involved in the autophagic pathway are important in the regulation of osteoclastogenesis, 66,67 indicating that this process participates both in bone formation and resorption. There is evidence that resorptive activity is decreased when bafilomycin, an autophagy inhibitor, is added to the culture of osteoclasts.…”
Section: Role Of Autophagy In Bone Biologymentioning
confidence: 99%
“…The involvement of autophagy in the proliferation and differentiation of osteoclasts, as well as the activity of bone absorption, has been proven (17)(18)(19). Autophagy was strongly activated in response to RANKL (20,21). Xiu et al (22) also reported the key role of RANKL in the formation of autolysosomes, subsequently promoting osteoclastogenesis.…”
mentioning
confidence: 99%